UPAYA PENINGKATAN HASIL BELAJAR MELALUI PENERAPAN MODEL PEMBELAJARAN RESIPROKAL DENGAN MEDIA BOLA CABANG OLAHRAGA PERMAINAN BOLA BASKET SISWA KELAS IX SEMESTER GANJIL SMP NEGERI 21 SURABAYA - Sumardi Sumardi (JURNAL EDUKASI: KAJIAN ILMU PENDIDIKAN, 2020)
The focus of the PTK problem is "Efforts to Improve Learning Outcomes Through the Application of Media Reciprocal Learning Models with Ball Balls for the IX Class Semester Students of Basketball Games in the Middle School 21 Surabaya Middle School." The formulation of the problem in this study are: Is the ball media and reciprocal / reciprocal learning model able to improve sports learning outcomes in basketball games, so that overall able to achieve the Minimum Completion Criteria (KKM). This classroom action research was conducted in conjunction with the lecturer practice program at the Surabaya 21st Junior High School. Previously it was preceded by observation for two days. The research procedure uses planning, implementation, evaluation, and reflection. Data collection techniques with test and observation methods, and the tools used during the study were ball media, field, basket basket, observation sheet. Data analysis technique with percentage formula. The results of the study are as follows: Average values ​​(Mean) are all above the KKM value which is equal to 70 and the average value is 75.5. This shows that the average student can master the learning material. There are obstacles due to the AULA fires in